ANALISIS PUSHOVER TERHADAP RESPON STRUKTUR DENGAN MENGGUNAKAN BASE ISOLATOR - Fitry Hasdanita; Mochammad Afifuddin; Muttaqin Muttaqin (Prodi Magister Teknik Sipil Unsyiah, 2018)
The earthquake-resistant building is a concept in construction technology that is in line with technology evolution. The idea of this earthquake-resistant concept is to reduce the seismic force that might work to the building structure instead of strengthening the structure itself. The structural component for reducing the earthquake force is called as a base isolator or seismic isolation. During seismic loading, this component is expected to accept and minimize the earthquake forces at a certain level without any significant damage to structure. This research is conducted to evaluate the response of the structure with base isolator. Then, the influence of base isolator on building structure is justified. Two (2) different types of structures, fixed base and base- isolated structure with a variety of post-yield stiffness (K2), were developed. The used type of base isolator is Lead Rubber Bearing (LRB). The analysis is conducted in accordance with pushover analysis method using SAP2000 v.19 program. The result suggested that the building structure with base isolator extends the natural period of the structure up to 1,380 times. The interstory drift of the base-isolated structure is smaller than the fixed base structure. The use of base isolator reduces the top displacement to an average of 21.93% for x- and 18.506% for y-direction. The overall structure performance evaluation of fixed base and base-isolated structures is at Damage Control level.